(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Annotation: In the 21st century, learning a new language, particularly English, has become a necessity in both professional and social contexts. Traditional methods of teaching, such as memorization and grammar drills, have long been used to impart language skills. However, as education evolves, innovative approaches like using games in the classroom are gaining traction. Language acquisition through games provides an interactive, enjoyable, and effective way to develop English proficiency. This article explores the best strategies for teaching English through games.